Evaluation of Psychometric Properties of Hardiness Scales: A Systematic Review - Sharif Nia, Hamid; Froelicher, Erika Sivarajan; Hosseini, Lida; Ashghali Farahani, Mansoureh (Frontiers in Psychology, 2022)
Background: Hardiness is one of the personality traits that can help individuals in stressful situations. Since human beings are constantly under stressful situations and the stresses inflicted on people in each situation are different, various scales have been developed for assessing this feature among different people in different situations. Hence, it becomes necessary for researchers and health workers to assess this concept with valid and reliable scales. This systematic review aims to rigorously assess the methodological quality and psychometric properties of hardiness scales. Method: In the first step, the databases including Scopus, PubMed, Web of science, and Persian databases were searched using suitable keywords without limitation time. We select eligible suitable studies after screening titles and abstracts. The quality of studies was evaluated using the Consensus based Standards for the selection of health Measurement Instruments (COSMIN) checklist and the Terwee quality criteria. Result: Of the 747 articles identified 33 articles were entered in this study. Based on the COSMIN checklist, the most reported properties were as following structural validity (84%), hypothesis testing (56%), content validity (42%), and internal consistency (39%). Furthermore, 12 studies reported cross-cultural validity, three studies criterion validity, and one study reported measurement error. Conclusion: The “family caregivers’ hardiness scale”, “Japanese Athletic Hardiness Scale”, “Occupational Hardiness Questionnaire”, and “Children’s Hardiness Scale” are the best tools to assessing hardiness in family caregivers, athletes, employees and children respectively. In addition, the “Dispositional Resilience Scale” (DRS-15) and The Personal Views Survey (PVS III-R) are the most frequently used scales with suitable features for measuring hardiness in the general population.